PENGEMBANGAN BAHAN AJAR DEEP LEARNING BERBANTUAN NEARPOD UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH STATISTIKA KELAS VIII - Thea Wilda Pamula Ananda Bagago; Syarifah Fadillah; Sandie (STKIP Subang, 2026)
This study aims to develop teaching materials based on a deep learning approach assisted by the nearpod platform to improve students' problem-solving abilities in statistics material for class VIII SMP Negeri 16 Pontianak. This research is a Research and Development (R&D) research and development using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques include indirect communication techniques and measurement techniques, with research instruments in the form of expert validation sheets, practicality questionnaires, pretest and posttest questions. The research sample is class VIII A consisting of 29 students. Data analysis techniques used include analysis of characteristics, validity, practicality, and effectiveness of the developed teaching materials. The results of the study showed that the interactive learning media developed reached the very valid category with a validity percentage of 95.83%, very practical with a practicality percentage of 92%, and effective with the results seen from the results of the paired t-test showing that t_count is greater than t_table, namely 32.456 > 2.048 if t_count > t_table then Ho is rejected (H₁ is accepted). Thus, the developed teaching materials effectively improve students' problem-solving abilities. Thus, teaching materials based on the deep learning approach assisted by the nearpod platform are suitable for use in the mathematics learning process in schools